EVALUASI IMPLEMENTASI SISTEM AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (SAKIP) (Studi Kasus Pada Pemerintah Kabupaten Kotawaringin Barat) - , Nunik Supartini, Dr. Bambang Riyanto, L.S., Akt., M.B.A. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The background of the research was the implementation of Governmental Institution Performance and Accountability System (SAKIP) by the government officers. Every government institution is required to be responsible for its main tasks and functions in managing the resources, executing the policies and programs, and producing accountability reports (LAKIP). However, the inability to implement SAKIP effectively in government institution is deemed as the cause of the low result of LAKIP evaluation. The purpose of the study is to determine the index and to classify the implementation rate and the obstacles faced by Kotawaringin Barat district in implementing SAKIP. It is a case study of comparing LAKIP SKPD to the criteria issued by Lembaga Administrasi Negara (LAN) No : 239/IX/6/8/2003. The material used were gathered from accountability reports (LAKIP) in 35 SKPD in Kotawaringin Barat district. The data were collected by means of documentchecking and interviewing some resource people related to the study. The highest implementation index was 88% and the lowest one was sebesar 52%. It is classified into 6 categories namely 1) Excellent ranging from 85%-91% consisting of 3 SKPD